Strong winds and widow makers : workers, nature, and environmental conflict in Pacific Northwest timber country - Beda, Steven C., 1980- (Urbana : University of Illinois Press, 2023)
"Often cast as villains in the Northwest's environmental battles, timber workers in fact have a connection to the forest that goes far beyond jobs and economic issues. Steven C. Beda explores the complex true story of how and why timber- working communities have concerned themselves with the health and future of the woods surrounding them. Life experiences like hunting, fishing, foraging, and hiking imbued timber country with meanings and values that nurtured a deep sense of place in workers, their families, and their communities. This sense of place in turn shaped ideas about protection that sometimes clashed with the views of environmentalists--or the desires of employers. Beda's sympathetic, in-depth look at the human beings whose lives are embedded in the woods helps us understand that timber communities fought not just to protect their livelihood, but because they saw the forest as a vital part of themselves"--
Introduction: A place in the forest -- Part I: Place. "The new empire" -- "The prodigal yield of the surrounding hills" -- "A goodly degree of risk" -- Part II: Power. "Conservation ... from the guys down below" -- "The many uses and values of forests" -- Part III: Problems. "Strong winds and widow makers" -- "Tie a yellow ribbon for the working man" -- "We keep carbon-eating machines healthy"
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 31, 2022).
eBooks on EBSCOhost
Keywords: Lumber trade -- Environmental aspects -- Northwest, Pacific; Lumbermen -- Northwest, Pacific -- Attitudes; Environmental economics -- Northwest, Pacific; POLITICAL SCIENCE / General; Environmental economics; Lumber trade -- Environmental aspects; Pacific Northwest; The environment; Environment and Ecology; Electronic books